2014
DOI: 10.1128/jcm.00266-14
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus GII.4 Detection in Environmental Samples from Patient Rooms during Nosocomial Outbreaks

Abstract: c Norovirus (NoV) is an important cause of nosocomial gastroenteric outbreaks. This 5-month study was designed to characterize NoV contamination and airborne dispersal in patient rooms during hospital outbreaks. Air vents, overbed tables, washbasins, dust, and virus traps designed to collect charged particles from the air were swabbed to investigate the possibility of NoV contamination in patient rooms during outbreaks in seven wards and in an outbreak-free ward. Symptomatic inpatients were also sampled. Nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 43 publications
0
40
0
2
Order By: Relevance
“…However, epidemic viruses such as influenza viruses, rotavirus (RV) and norovirus (NV) have been shown to be able to adhere and contaminate inert surfaces as well as medical devices close to the patients' environment [10][11][12]. NV and RV were shown to be particularly resistant; they can survive for weeks, even months, on surfaces and in the hospital environment [11,[13][14][15][16]. Contamination of hospital surfaces by these viruses may therefore play a role in nosocomial epidemics [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, epidemic viruses such as influenza viruses, rotavirus (RV) and norovirus (NV) have been shown to be able to adhere and contaminate inert surfaces as well as medical devices close to the patients' environment [10][11][12]. NV and RV were shown to be particularly resistant; they can survive for weeks, even months, on surfaces and in the hospital environment [11,[13][14][15][16]. Contamination of hospital surfaces by these viruses may therefore play a role in nosocomial epidemics [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…16,1922 A study of environmental samples from outbreak-affected hospital wards found GII norovirus on almost half of the swabs, including in dust and on surfaces. 23 Once the virus is ingested, there is an incubation period of between 12 and 48 h, after which infected persons generally experience acute onset of symptoms of gastroenteritis, such as vomiting, diarrhoea, abdominal cramps, as well as systemic symptoms, including fever. However, 20–30% of infected individuals may remain asymptomatic.…”
Section: Biology and Transmission Characteristicsmentioning
confidence: 99%
“…Indoor air, in particular, can expose us to noxious chemicals, particulates, and a variety of infectious agents, as well as pollen and other allergens. 4,5 Emerging pathogens, such as noroviruses 6 and Clostridium difficile, 7 have also been detected in indoor air, with a strong potential for airborne dissemination. Pathogens discharged into the air may settle on environmental surfaces, which could then become secondary vehicles for the spread of infectious agents indoors.…”
mentioning
confidence: 99%